Trade Shocks and Credit Reallocation - Federico, Stefano; Hassan, Fadi; Rappoport, Veronica (American Economic Review, 2025)
This paper identifies a credit-supply contraction that arises endogenously after trade liberalization. Banks with loan portfolios concentrated in sectors exposed to competition from China face an increase in nonperforming loans after China’s entry into the World Trade Organization. As a result, they reduce the supply of credit to firms, irrespective of the firm’s sector of operation. This cut in credit translates into lower employment, investment, and output. Through this mechanism, the financial channel amplifies the shock to firms already hit by import competition from China and passes it on to firms in sectors expected to expand upon trade liberalization. (JEL D22, F14, G21, G31, G32, L25, P33)